"Regaining the Future by Rebuilding the past?". The Question of Intergenerational Transfer and Production of Cultural, Economic and Social Capital by Women in Poland after the Second World War. Issue 6 (18th August 2021) - Skórzyńska, Izabela Dorota
Abstract: In this article I followed the life stories of five Polish women born between 1939–1949. The key question concerned the intergenerational transmission of socio-cultural and economic capitals, inherited and passed by my narrators under the conditions of a socialist state. By answering this question, I took into account three variables: the first concerns the different positions and capitals of narrators and their families before the WW2; the second concerns the war and its destructive impact on the economic situation of the narrators; the third, the most important, concerns (re)building of the capitals of the narrators living in the condition of the socialist state. An in-depth analysis the life stories of the narrators led me to the following conclusions: (1) even though the families of the narrators had only small capitals before WW2, they (re)built them and multiplied, creating conditions for further development of their generational children after the war; (2) the socialist state made educational and professional development possible for the narrators and they took advantage of these opportunities; (3) the narrators were causative in the (re-) construction and transmission of their capitals, also when the socialist state torn by economic and political crises, had failed them.